2007
DOI: 10.1007/s00395-007-0653-4
|View full text |Cite
|
Sign up to set email alerts
|

SCH 79797, a selective PAR1 antagonist, limits myocardial ischemia/reperfusion injury in rat hearts

Abstract: Myocardial ischemia/reperfusion (I/R) injury is partly mediated by thrombin. In support, the functional inhibition of thrombin has been shown to decrease infarct size after I/R. Several cellular responses to thrombin are mediated by a G-protein coupled protease-activated receptor 1 (PAR1). However, the role of PAR1 in myocardial I/R injury has not been well characterized. Therefore, we hypothesized that PAR1 inhibition will reduce the amount of myocardial I/R injury. After we detected the presence of PAR1 mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 24 publications
1
67
2
1
Order By: Relevance
“…35 Interestingly, although the PAR1-knockout mice exhibited no difference, administration of the PAR1 antagonist SCH79797 was found to reduce infarct size. 36 Likewise, PAR2 activating peptides were also found to exhibit the reverse response when administered to a mouse model of IR. 37,38 Whether the differential effects of the inhibitors versus the knockout are due to nonspecificity of the inhibitor or compensatory mechanisms related to PAR1 or PAR2 deficiency requires further elucidation.…”
Section: Ischemia Reperfusion Results In Elevated Protease Activity Tmentioning
confidence: 99%
“…35 Interestingly, although the PAR1-knockout mice exhibited no difference, administration of the PAR1 antagonist SCH79797 was found to reduce infarct size. 36 Likewise, PAR2 activating peptides were also found to exhibit the reverse response when administered to a mouse model of IR. 37,38 Whether the differential effects of the inhibitors versus the knockout are due to nonspecificity of the inhibitor or compensatory mechanisms related to PAR1 or PAR2 deficiency requires further elucidation.…”
Section: Ischemia Reperfusion Results In Elevated Protease Activity Tmentioning
confidence: 99%
“…In contrast, a recent study found that inhibition of PAR-1 with a selective PAR-1 antagonist reduced infarct size in a rat model of cardiac I/R injury. 23 This difference could be due to the use of different models of I/R injury or off-target effects of the antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacology of PARs is not well developed, and inhibitors capable of blocking PAR1 function in mouse models have not been well characterized with respect to off-target effects. Nonetheless, SCH79797 has been used to probe PAR1 function in rodent models (31)(32)(33); thus, encouraged by the protection against IAV seen in Par1 -/-mice, we examined the effects of this compound on the course of IAV infection. SCH79797 inhibited PAR1-AP-induced ERK activation in mouse NIH3T3 cells ( Figure 4A), which suggests that it is capable of blocking signaling by the mouse homolog of PAR1.…”
Section: Par1 Contributes To the Pathogenesis Of Iav Infectionmentioning
confidence: 99%